Pediatric Tuberculosis: 12 Years of Experience in a Tertiary Referral Center in Portugal - Borges, Madalena (2022)
Introduction: The diagnosis of tuberculosis in children is a challenge namely because extrapulmonary tuberculosis and severe disease are more frequent in this age group. The aim of this study was to evaluate and reflect about severe tuberculosis in pediatric age, in a metropolitan area of Lisbon.Material and Methods: Descriptive study about patients under 18 years of age admitted with tuberculosis disease in a tertiary pediatric hospital, from 2008 to 2019 (12 years).Results: We report 145 patients, average of 12 cases/year, with an increase in the last three years. Median age of 12.9 years, 42.8% born in Portuguese-speaking African countries and 20% had a chronic disease. The diagnosis was pulmonary tuberculosis in 52.4% (n = 76) and extrapulmonary tuberculosis in 47.6%: lymphatic (n = 26), skeletal (n = 15), miliary (n = 8), meningeal (n = 7), peritoneal/ intestinal (n = 6), pleural (n = 4), renal (n = 1), cutaneous (n = 1), thoracic wall (n = 1) and salivary glands (n = 1). The tuberculin test was positive in 78/99 (78.8%) and Interferon Gamma Release Assay in 61/90 (67.8%). In 20.7% (n = 30) acid-fast bacilli were identified in gastric aspirate/sputum and the agent was identified in 59.3% (n = 86). Tuberculosis was resistant in 11% (n = 16). Patients with extrapulmonary tuberculosis were younger (p = 0.006) and had more prolonged therapy (p < 0.001). Therapy-related complications occurred in 11% (n = 16). One patient died (with terminal cancer).Conclusion: This study highlights the need for screening of tuberculosis in children from endemic countries, patients with immunosuppression and chronic disease.